Pengaruh Service Quality, Relationship Marketing, Customer Experience terhadap Customer Satisfaction: (Study pada Pengguna Jasa Wifi Cv. Network Maha Jaya di Desa Bakalan Purwosari) - Sofi syaeffulloh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In the era of globalization, business competition is getting tighter cause marketing activities and management of a company are encouraged to follow the development in order to maintain the continuity of the company. CV. Network Maha Jaya to do relationship marketing to satisfy and establish good relationships with customers. Good relationship marketing efforts can assist companies in understanding the wants and needs so that the company can satisfy and build loyalty of the customers to always be loyal to the company within the period ahead. This study aims to analyze the influence of relationship marketing on customer satisfaction and customer loyalty Kompas newspaper in Surabaya. This study used a descriptive quantitative research methods and data collection techniques by sampling from questionnaires.